The Role of Information Technology in the Context of OVO Digital Wallet Attractiveness - Utomo, Sulistyo Budi; Pranawukir, Iswahyu; Ramadhan, Abid; Judijanto, Loso; Ilham, Ilham (Universitas Dharma Wacana, 2023)
The research aims to find out the attractiveness of Ovo so that people use Ovo more than other digital wallets in payment transactions. The research uses a qualitative method, with triangulation of data sources, namely observation, interviews and documentation. Informants in the research are people who have knowledge in the topic under study. Data analysis is in the form of data reduction, data presentation and conclusion drawing. The results showed that in the midst of a lot of competition, Ovo is aggressively conducting sales promotions in the form of cashback and vouchers so that consumers feel they get more benefits by using Ovo compared to other digital wallets. Ovo is superior because it has an easy feature in topping up the balance without additional administration fees that other digital wallets do not have. In addition, the attraction of Ovo is that it has a transfer feature to banks without additional administration fees. This is a favourite feature of Ovo users themselves. Currently, hundreds of merchants have partnered with Ovo. Ovo offers convenience in its features, making it easier for consumers to carry out their activities. More practical, faster and easier transactions. The presence of Ovo provides benefits such as shortening payment time, no need to carry or store large amounts of cash.